Efficacy of a Workplace Intervention Program With Web-Based Online and Offline Modalities for Improving Workers' Mental Health - Lam, Lawrence T.; Lam, Mary K.; Reddy, Prasuna; Wong, Prudence (Frontiers in Psychiatry, 2022)
Objective This study aims to examine the efficacy of the Workplace Web-based blended psychoeducation mental health intervention program intervention program. Of particular interest is the short-term effect of the intervention on workplace burnout, stress, quality of life, and the mental health literacy of workers. Methods and Materials The study focused on employees (n=456) in specific industries with high levels of work-related stress, adopting a phase III wait-listed cluster randomised controlled trial. Work-related burnout was assessed by the Maslach Burnout Inventory (MBI) and stress was measured using the stress subscale of the Depression, Anxiety, and Stress scale (DASS). Quality of Life was evaluated by the European Quality of Life-5 Dimensions (EQ-5D-5L) and Mental Health Literacy was assessed using the Australian National Mental Health Literacy and Stigma Survey. Data were analysed as a trial with intention-to-treat analysis and adjustment for the clustering effect of work sites. Results Significant differences between intervention and control groups were found on all outcome measures except the self-rated quality of life. The intervention group displayed a significant reduction in the weighted mean score of about 1.0 units (s.e.=0.4) on the stress scale (p=0.015) and an increase in the weighted mean score of 1.9 units (s.e.=0.9) in the professional accomplishment domain of the MBI (p=0.035). Significant increases were found in the weighted mean scores in the intervention group for correct recognition of the mental problems, help-seeking, and stigmatisation, in comparison to the control group who scored 0.2 (s.e.=0.1), 0.9 (s.e.=0.2), 1.8 (s.e.=0.4) respectively. Conclusions The results obtained from a comparison of the outcome measures between the intervention and control groups were statistically significant, indicating that the intervention group performed better on most measures. The study demonstrates that, in the short term. the on-and-offline modalities of the Web-based blended psychoeducation intervention program is efficacious in reducing workplace burnout and stress and promoting mental health literacy at the workplace.